2018
DOI: 10.1111/joor.12748
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and temporomandibular joint and facial pain in the general population

Abstract: Summary Background Associations of alexithymia with temporomandibular pain disorders (TMD), facial pain, head pain and migraine have been described, but the role of the different dimensions of alexithymia in pain development remained incompletely understood. Objectives We sought to investigate the associations of alexithymia and its subfactors with signs of TMD and with facial pain, head pain and migraine in the general population. Methods A total of 1494 subjects from the general population completed the Toro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In this line, it has been observed that the inability to express feelings with mimics may interfere in the ones' own recognition of emotions [92]. A recent study has found a moderate-to-strong association between face and head pain and alexithymic features [101]. Alexithymia is a personality trait based in an intrinsic difficulty in recognizing the emotional components of subjective experiences (emotion recognition and expression) [102].…”
Section: Consequences Of the Sensorimotor And Emotional Disturbances In Cofpmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line, it has been observed that the inability to express feelings with mimics may interfere in the ones' own recognition of emotions [92]. A recent study has found a moderate-to-strong association between face and head pain and alexithymic features [101]. Alexithymia is a personality trait based in an intrinsic difficulty in recognizing the emotional components of subjective experiences (emotion recognition and expression) [102].…”
Section: Consequences Of the Sensorimotor And Emotional Disturbances In Cofpmentioning
confidence: 99%
“…Patients with alexithymia suffer from higher psychopathological distress [103], and it is often stated in connection with chronic pain syndromes [104]. Therefore, it seems to be an important contributing factor in the development of a chronic facial pain [101]. Causes of alexithymia are unknown.…”
Section: Consequences Of the Sensorimotor And Emotional Disturbances In Cofpmentioning
confidence: 99%
“…When there are various areas of pain afflicting one individual, the distress increases and interferes in the identification and description of feelings. 33,34 Therefore, individuals with chronic pain should undergo psychotherapeutic treatment that enable them to break down this vicious circle by improving their ability to detect and distinguish emotions and bodily sensations. 20,35 The importance to consider psychotherapy also relies on the fact alexithymia could result in hypervigilance, increasing somatic sensations and inducing high levels of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Kappa values for detecting tenderness upon palpation of the masticatory muscles and the temporomandibular joint ranged from 0.53 to 0.63. Training of the dentists and consensus discussions occurred before the start of the examinations and were repeated for calibration twice a year during the period of data collection 31 …”
Section: Methodsmentioning
confidence: 99%